Evaluación del manual virtual para prevención de caries en adultos creado para la Facultad de Odontología de la universidad de las Américas - Guachamín Catota, Viviana Carolina (2016)
The research was conducted at the dental clinic of Universidad de las Américas in order to assess the effectiveness of the virtual handbook installed at the clinic, which aims to prevent tooth decay in those adults who visit it. Since the handbook mentioned consists of two parts, this study proposes the merge and modification, if needed, of both parts. Therefore, this project is a comparative study since it measures and compares the knowledge patients had about oral health before and after the intervention of both handbooks, the former and the modified, to test its individual effectiveness. For this reason, the present study is planned in three parts. The first part, held in December 2015, was a diagnostic phase which involves collecting information about the former virtual handbook, through surveys, to detect deficits in its content and its information delivery. The sample was taken on teachers, students, and patients of the clinic. As a result, the surveys established that the former handbook had the right theoretical content, but the way it delivered the information was at fault. The second part of this study, on the other hand, consists of the development of a new handbook that unifies and modifies both parts of the former handbook according to the results of the diagnostic phase. Therefore, the new handbook enhanced the interactivity, multimedia, and the use of a suitable language for patients. Finally, the third part of this study consists of the evaluation and contrast of both handbooks through surveys. The sample taken was on 120 adult patients who attended to the clinic on January 2016. These surveys assessed the knowledge acquired by the patients that used both virtual handbooks and included a subjective evaluation for the content and aesthetic of each handbook. In conclusion, the effectiveness of the new handbook was better that its predecessor since it increased the retention of information in 25 percent, compared to the former handbook, and the 95.85 percent of patients that used the new handbook answered correctly to all the questions made in the survey.